2006
DOI: 10.1016/j.ast.2006.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and optimization of stall control for an airfoil with a synthetic jet

Abstract: This study concerns the simulation and optimization of stall control, using a synthetic jet. The flow is simulated by solving unsteady Reynolds-averaged Navier-Stokes equations with a near-wall low-Reynolds number turbulence closure. The flow around a NACA 0015 airfoil, including a synthetic jet located at 12% of the chord, is studied for a Reynolds number Re = 8.96 10 5 and for angles of attack from 12 to 24 degrees. The optimization of the control parameters (momentum coefficient, frequency, angle w.r.t. the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 16 publications
2
18
0
1
Order By: Relevance
“…One can remark that the DBD actuation seems contribute to only one flow structure contrary to flow control performed by synthetic jets. Indeed, it was experimentally [44] and numerically [45] demonstrated that the lift increase observed for stall control by synthetic jet is due to the creation of two or three vortices convected along the suction side of a NACA 0015 airfoil. Phase-averaged PLIF visualisations have also demonstrated that the coherent structures responsible for the apparent reattachment could coalesce to form a single, more intense vortex synthetic [46].…”
Section: Reattachment Process By Non-thermal Plasma Actuatormentioning
confidence: 99%
“…One can remark that the DBD actuation seems contribute to only one flow structure contrary to flow control performed by synthetic jets. Indeed, it was experimentally [44] and numerically [45] demonstrated that the lift increase observed for stall control by synthetic jet is due to the creation of two or three vortices convected along the suction side of a NACA 0015 airfoil. Phase-averaged PLIF visualisations have also demonstrated that the coherent structures responsible for the apparent reattachment could coalesce to form a single, more intense vortex synthetic [46].…”
Section: Reattachment Process By Non-thermal Plasma Actuatormentioning
confidence: 99%
“…Among the many optimization strategies available (e.g., finite difference or adjoint-based gradients and descent, simulatedannealing [41], simplex or multidirectional search [28]), a derivativefree, genetic algorithm (see Fig. 2 for an overview), GADO [42], was preferred for the following reasons:…”
Section: Optimizermentioning
confidence: 99%
“…As a possible answer [28,29], a completely automated, surrogate-based optimization [30,31] algorithm was developed and applied to the design of a two-dimensional high-lift system with a conventional slotted slat and a simply hinged, slotless flap. The process will now be described in detail and results for a continuously blowing slot will be presented.…”
mentioning
confidence: 99%
“…The actuation frequencies are in the kHz range and are related to the airflow speed [10]. Most of the literature focuses on fixed wind tunnel test [10] but simulations show a potential increase in the maximum lift of an airfoil by 34% with an increase in the maximum stall angle of a profile [17]. These characteristics make synthetic jets system very promising for improving the characteristics of a profile for helicopter applications.…”
Section: Active Flow Controlmentioning
confidence: 99%